Performance of transplanted maize (Zea mays) under varying age of seedling and method of nursery raising in the midlands of eastern region - KUMAR, SANJEEV; SHIVANI; KUMAR, SANTOSH (The Indian Journal of Agricultural Sciences, 2014)
Field experiments were conducted at ICAR Research Complex for Eastern Region Farm, Patna during winter (rabi) season of 2008-09, 2009-10 and 2010-11 to study the performance of maize (Zea mays L.) crop under transplanted condition as affected by different age of seedlings and methods of nursery raising. Transplantation of five weeks old seedlings and nursery raised on sand culture as well as on raised bed recorded more plant height, leaf length, dry matter accumulation/plant and yield attributes over other methods of raising seedlings and varying age group. After transplantation mortality of seedlings in the main field was minimum reported with 5 week old seedlings (5.8%) as well as seedlings raised under sand culture and raised bed method (5.2% and 5.8%, respectively) during the years of experimentation. Transplanting of five weeks old seedlings raised either in sand culture or on raised beds produced significantly higher grain yield (6.71 and 6.36 tonnes/ha, respectively) over other treatments. Root volume and leaf area index (LAI) at 90 days after transplanting (DAT) were also higher in seedlings raised under sand culture (1.03and 72.2 cm3) and raised bed conditions (0.99 and 69.8 cm3) in nurseries. However, 5 week old seedlings grown either on sand culture or on raised bed resulted higher net income (Rupees 23 074 and 22 334/ha respectively). It was also observed that transplanted crop matured 10-12 days earlier than direct seeded maize.